2011
DOI: 10.1111/j.1365-2729.2011.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the learning‐theory foundations of game‐based learning: a meta‐analysis

Abstract: Past studies on the issue of learning‐theory foundations in game‐based learning stressed the importance of establishing learning‐theory foundation and provided an exploratory examination of established learning theories. However, we found research seldom addressed the development of the use or failure to use learning‐theory foundations and categorized these learning theories into relative types and synthesized their development. We investigate this issue from the perspective of learning theories invoked to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(128 citation statements)
references
References 63 publications
3
106
0
6
Order By: Relevance
“…Although other works looked into the learning theory foundations of gamebased learning [46], one major limitation of previous dashboard reviews is that none investigate the connection to learning sciences. Moreover, [35] and [4] provide recommendations for the design of learner dashboards, but none suggest the use of educational concepts as a basis for the design or evaluation of the dashboards.…”
Section: Introductionmentioning
confidence: 99%
“…Although other works looked into the learning theory foundations of gamebased learning [46], one major limitation of previous dashboard reviews is that none investigate the connection to learning sciences. Moreover, [35] and [4] provide recommendations for the design of learner dashboards, but none suggest the use of educational concepts as a basis for the design or evaluation of the dashboards.…”
Section: Introductionmentioning
confidence: 99%
“…These theories are also the fundament for game-based learning (Wu et al, 2012), where systematic approaches towards the design of applications have already been explored with respect to delivering / providing the needed skills (Johnson et al, 2011), the motivational potential (Carstens & Beck, 2010;Douch, & Savill-Smith, 2010) as well as their ability to address various target groups in the most effective way (Unterfauner et al 2010;Liao et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Electronic game developers have applied constructivist theory to create meaningful educational learning experiences for gamers [2]- [9]. Findings from studies of game design and the use of constructivist principles to design games yielded stronger games that had greater educational value and meaning for the players, affirming the position posited by Piaget.…”
Section: B Gaming and Constructivismmentioning
confidence: 88%
“…Findings from studies of game design and the use of constructivist principles to design games yielded stronger games that had greater educational value and meaning for the players, affirming the position posited by Piaget. Gaming researchers examined the effective use of constructivist theory and found that game design was enhanced and learning more apparent when the theory was applied [9]- [13].…”
Section: B Gaming and Constructivismmentioning
confidence: 99%